Diet–microbial cross–talk underlying increased visceral perception - Giada De Palma; David E. Reed; Premysl Bercik (Gut Microbes, 2023)
ABSTRACTVisceral hypersensitivity, a fundamental mechanism of chronic visceral pain disorders, can result from both central or peripheral factors, or their combination. As an important regulator of normal gut function, the gut microbiota has been implicated as a key peripheral factor in the pathophysiology of visceral hypersensitivity. Patients with chronic gastrointestinal disorders, such as irritable bowel syndrome, often present with abdominal pain secondary to adverse reactions to dietary components. As both long- and short-term diets are major determinants of gut microbiota configuration that can result in changes in microbial metabolic output, it is becoming increasingly recognized that diet–microbiota interactions play an important role in the genesis of visceral sensitivity. Changes in pain signaling may occur via diet-induced changes in secretion of mediators by both the microbiota and/or host cells. This review will examine the peripheral influence of diet–microbiota interactions underlying increased visceral sensitivity.